エンダービーランド ノ チガク チョウサ ノ テンボウ ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 金尾, 政紀; カナオ, マサキ; Kanao, Masaki (1999)
P(論文) 「エンダービーランドの地学調査の展望に関する研究小集会」が1998年9月8日, 国立極地研究所にて開催され, 所内外から34名が参加した。第39次日本南極地域観測隊(39次隊 : 1998年)夏隊により行われた, トナー島の地質調査の詳細な報告が, スライドやビデオを交えて行われ, 島全域の地質図が初めて示された。また, 第40次隊(1999年)で予定している小型ヘリコプターを用いての地質・地形調査の詳細な計画が報告され, オペレーション実行上の安全対策等, 各種問題点について議論した。観測隊出港までにさらに具体的な詰めを行うことにした。第41次夏隊(2000年)で実施予定の人工地震探査は, 環境アセスメントの観点よりトナー島露岩域での探査ではなく, みずほ高原の大陸氷床上での実験に切り替えることで参加者の了解を得た。第42次隊(2001年)以降のアムンゼン湾-ケーシー湾にかけての長距離測線による人工地震探査については, 小型ヘリコプター導入における諸問題点を含めて, 今後第VI期計画と絡めて改めて議論することになった。本報告では, 南極域における人工地震探査の環境アセスメントの問題に特に重点を置いて記載する。 A workshop on "Prospects on the Earth Science Program in Western Enderby Land" was held on September 8,1998 at the National Institute of Polar Research, with 34 participants. The future program of earth sciences in Enderby Land, entitled "Structure and Evolution of the East Antarctic Lithosphere (SEAL Project)" was discussed, considering both scientific significance and logistic problems. First, the details of geological surveys in the Tonagh Islands were reported by the 39th Japanese Antarctic Research Expedition (JARE-39) in 1998,followed by the planning of the JARE-40 party in 1999,using two helicopters over wide areas of Western Enderby Land. Second, seismic explosion experiments by JARE-41 in 2000 were planned to be held on the Mizuho Plateau icesheet. The location of seismic lines was changed from Tonagh Island, because of the danger of environmental impact on the vegetation and alteration of outcrops. Finally, a proposed large-scale seismic experiment across the geological boundary between the Napier and the Rayner Complexes using helicopters was determined to face operational difficulties and will be discussed laterly in relation to future plans of JARE. This report is focused on the environmental acessment for seismic explosion experiments in the Antarctic region. departmental bulletin paper